Solar Photovoltaic Technology In Brazil - Juliana de Almeida Yanaguizawa LUCENA; Victor Gabriel Bezerra de HOLANDA (Indonesia Strategic Sustainability, 2022)
In recent years, the use of solar systems has been increasing worldwide in an accelerated rate, with perspective of staying among the main sources of renewable energy for the following decades, along with wind power. The photovoltaic energy in Brazil currently represents 4,5 GW (2,5% of the national electric matrix).Â Solar thermal energy is called when solar radiation is used to transfer energy to a medium, usually water or air. It is a renewable, sustainable and environmentally friendly source of energy. The number of solar thermal energy applications is very extensive when considering all temperature levels and energy demands. In this context, the present work shows the evolution of solar photovoltaic energy in Brazil, bringing a discussion regarding to solar power characteristics, working principles and different technologies of solar cells, as well as aspects of operation and maintenance of the photovoltaic panels. Investments in research for the development of new technologies and valuation of existing ones for solar energy should also be prioritized, as well as for better planning and sustainable use of photovoltaic energy, given the advantages for the economy, society and the environment provided by this renewable and clean source.